Intensive investments in intellectual:the way to increase sustainable - Lopes, Ilídio Tomás (2010)
This paper aims to highlight the need to monitor the macroeconomic innovation effort and diagnose its linkage with business returns. It constitutes a basic approach about intellectual property as a key driver towards better strategic and financial performance achievements.